2000
DOI: 10.1149/1.1393317
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Electrodeposition of Cu[sub 2−x]Se and CuInSe[sub 2] Thin Films by the Induced Co-deposition Mechanism

Abstract: The induced co-deposition mechanism in one-step electrodeposition of Cu 2Ϫx Se and CuInSe 2 thin films was investigated. Cu 2Ϫx Se and CuInSe 2 thin films were deposited potentiostatically on Mo substrates by a one-step process from an acidic electrolyte containing SCN Ϫ ions as complexing agents. The films were examined by scanning electron microscopy, energy dispersive X-ray spectrometry, X-ray diffraction, and ion beam analysis methods. Good control of stoichiometry was achieved over a wide potential range,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
65
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 47 publications
8
65
0
Order By: Relevance
“…(5)) [21] and this reduction feature shows a significant positive shift (from À0.85 V to À0.64 V). This positive shift may be explained by the generation of CuSe according to Eq.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…(5)) [21] and this reduction feature shows a significant positive shift (from À0.85 V to À0.64 V). This positive shift may be explained by the generation of CuSe according to Eq.…”
Section: Resultsmentioning
confidence: 96%
“…Employing complexing agents is one of the most effective methods for this task. Many complexing agents, have been studied in electrodeposition of CIS and CIGS, including citrate [15,16], triethanolamine [17,18], ethylene diamine [19], thiocyanate [20,21], EDTA [22], benzotriazole [23] and so on. These complexing agents are widely used in basic copper plating baths and can form stable complexes with copper in basic solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Kemell et al reported that CuSe phase enables the incorporation of In 3+ ions by induced co-deposition process [110]. Chassaing and co-workers reported that In 3+ inclusion takes place when the [Se/Cu] ratio is greater than 1 to form CuInSe 2 .…”
Section: Electrochemical Formation Mechanism Of Cise/cigsementioning
confidence: 99%
“…Various electorodeposition processes have been studied in an attempt to attain a CIS-based film with smooth surface, suitable stoichiometry, compact crystalline, and large grain size [25][26][27][28][29][30]. CIS-based film with Cu-rich stoichiometry usually has a smooth surface and compact crystalline with large grain size [31,32].…”
Section: Introductionmentioning
confidence: 99%